The Changing Face of the Cornea in a Case of Juvenile Glaucoma and Subclinical Keratoconus - Khalil, Ahmad K. (Klinische Monatsblätter für Augenheilkunde, 2022)
We report on a 23-year-old man who presented with bilateral subclinical keratoconus and juvenile glaucoma (JG). With intraocular pressures (IOPs) of 30 and 28 mmHg, both eyes were consecutively operated by adjusted trabeculotomy, leading to a remarkable decrease in IOP to well below the mean for this surgery in JG. Meanwhile, most keratoconus indices clearly progressed in the first 5 months postoperatively, with increases in corneal hysteresis, associated with a remarkable drop in the corneal resistance factor. During the following years, IOP remained low, and all changes (except the increase in corneal hysteresis) reverted to near preoperative levels through the follow-up course of 5 years. This report complements a few existing reports that show the coincidence of keratoconus and JG, and, more importantly, documents a novel pattern of remarkable and prolonged corneal changes following surgical lowering of IOP in eyes with these changes. Postoperative biomechanical disturbances in the cornea and possibly limbus are proposed in cases of JG and subclinical keratoconus.
Keywords: juvenile glaucoma; keratoconus; biomechanics; cornea; hypotony